Integrated Postsecondary Education Data System (IPEDS): Higher Education Finance Data, 1991-1992 ([Verlag nicht ermittelbar], 2000)
This data collection contains information on finances for a sample of postsecondary institutions in the United States, the District of Columbia, and its outlying areas (American Samoa, Guam, Puerto Rico, the Virgin Islands, and the Marshall Islands). The finance data, collected annually, are used for reporting and projecting capital outlays of two-year and four-year colleges and universities, trends in replacements of plant assets, and performance of endowment funds. Part 1, Institutional Characteristics, includes variables on control and level of institution, religious affiliation, highest level of offering, Carnegie classification, and state FIPS codes and abbreviations. Part 2, Current Funds Revenues by Source (Part A of the survey), provides each institution's current funds revenues by source (e.g., tuition and fees, government, gifts). Part 3, Current Funds Expenditures by Function (Part B), covers expenditures for instruction, research, and plant maintenance. Part 4, Clarifying Questions Regarding Total E&G Expenditures and Revenues (Part C of the survey), contains information on total E&G revenues and expenditures to determine what is included/excluded from reported current funds expenditures. Part 5, Utility Expenditures (Part D), reports all expenditures for utilities in the operation and maintenance of the plant, auxiliary enterprises, and independent operations, excluding expenditures for hospitals. Part 6, Scholarship and Fellowship Expenditures by Source (Part E), covers scholarships, defined as grant-in-aid, trainee stipends, tuition and fee waivers, and prizes to undergraduate students, and fellowships given to graduate students. Part 7, Library Acquisitions (Part F), covers costs involved in acquisition of library materials. Part 8, Indebtedness on Physical Plant (Part G), reports data on indebtedness liability against the physical plant, including auxiliary enterprises facilities as well as educational and general facilities, excluding debt issued and backed by the state government. Part 9, Details on Endowment Assets (Part H), provides information on the amounts of gross investments of endowment, term endowment, and funds functioning as endowment for the institution, and any of its foundations and other affiliated organizations. Part 10, Changes in Funds Balances (Part I), includes both unrestricted and restricted funds balances. Part 11, Hospital Revenues (Part J), reports the revenues for, or generated by, major public service hospitals over which the institution has fiscal control (not the medical school). Part 12, Physical Plant Assets (Part K), reports the values of land, buildings, and equipment owned, rented, or used by the institution.